IMPLEMENTASI E-BUDGETING DAN DAMPAKNYA TERHADAP KETERBUKAAN INFORMASI KEUANGAN DISEKTOR PEMERINTAHAN KABUPATEN BANDUNG - Fanesya Islami Zahra; Syifa Shafira; Abdal Abdal (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The implementation of e-Budgeting in Bandung Regency has had a significant positive impact on improving transparency, accountability, and the effectiveness of local financial management. This digital system allows the public to easily access budget information through official government platforms, thereby strengthening the oversight role of both the public and formal institutions. Additionally, data integration within e-Budgeting improves the accuracy of budget preparation, accelerates synchronization among local government agencies, and supports the implementation of audit trails as internal control mechanisms. From a good governance perspective, e-Budgeting serves as a crucial foundation for strengthening performance-based governance that is more open and responsive. Nevertheless, challenges such as low digital literacy among government officials, limited IT infrastructure, and the public’s limited understanding of budget information remain obstacles that must be addressed. Efforts to enhance human resource capacity and improve technological support are key to optimizing the system in the future. Overall, the implementation of e-Budgeting in Bandung Regency has brought about a transformation in budget management toward a system that is more transparent, efficient, and integrity-driven.